2020
DOI: 10.1073/pnas.2006526117
|View full text |Cite
|
Sign up to set email alerts
|

A structural framework for unidirectional transport by a bacterial ABC exporter

Abstract: The ATP-binding cassette (ABC) transporter of mitochondria (Atm1) mediates iron homeostasis in eukaryotes, while the prokaryotic homolog from Novosphingobium aromaticivorans (NaAtm1) can export glutathione derivatives and confer protection against heavy-metal toxicity. To establish the structural framework underlying the NaAtm1 transport mechanism, we determined eight structures by X-ray crystallography and single-particle cryo-electron microscopy in distinct conformational states, stabilized by individual dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 58 publications
7
53
1
Order By: Relevance
“…Previously Atm1/ABCB7/HMT1/ABCB6 subfamily model built by NaAtm shows that apo-form contains only one cavity for substrate binding 31 , 32 . In the apo-state, hABCB6 adopts an inward-facing conformation and TMDs of hABCB6 contain the substrate-binding cavity which is divided into two parts: a closed cavity 2 and an open-form cavity 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously Atm1/ABCB7/HMT1/ABCB6 subfamily model built by NaAtm shows that apo-form contains only one cavity for substrate binding 31 , 32 . In the apo-state, hABCB6 adopts an inward-facing conformation and TMDs of hABCB6 contain the substrate-binding cavity which is divided into two parts: a closed cavity 2 and an open-form cavity 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of events in the transmembrane region resulting in the efflux of the substrate remains to be clearly elucidated. Structural studies of the bacterial transporters Atm1 and TmrAB have shown that the conformational landscape of these transporters is rather complex [3,4]. Figure 5A is a schematic representation of a possible mechanism showing conformational changes that occur in WT and EQ mutant P-gp during the ATP hydrolysis cycle and the Table in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the IC conformation the NBDs dimerize, and the transmembrane region is rearranged, expelling the substrate from the cell [1]. It is clear that this is an oversimplified model and that transporters actually undergo many different conformational changes during the ATP‐coupled transport cycle, as recently shown for the bacterial transporters Atm1 and TmrAB, for which at least eight different conformations were solved using X‐ray crystallography and cryo‐electron microscopy (cryo‐EM), respectively [3,4]. For instance, it has been proposed that the ADP and vanadate (V i )‐trapped conformation of P‐gp resembles the transition state during the hydrolysis of ATP [5], yet such a conformation has yet to be solved.…”
mentioning
confidence: 99%
“…G1 assumes a closed conformation when ATP binds the NBS, which collapses site 1 while simultaneously pushing the neutral sterol substrate to the extracellular cavity, where it binds extracellular lipid acceptors or enters the outer hemileaflet of the bilayer. Upon extracellular cholesterol release and ATP hydrolysis, the transporter returns to the resting state, ready to transport another cholesterol molecule ( 35 , 42 44 ). Further structural analysis of G5G8 will be required to determine how ATP hydrolysis can rearrange the TMHs so that it flips from an inward- to an outward-facing state, as has been found to occur in other ABC transporters.…”
Section: Cholesterol Transport By G1 and G5g8mentioning
confidence: 99%